Resiliensi Ibu Penderita Postpartum Syndrome di Desa Laut Dendang - Nafilah, Husna; Metia, Cut (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2024)
This study aims to analyze the phenomenon related to the analysis of resilience in mothers with postpartum syndrome in Dusun V Cempaka Laut Dendang. In this study, data were taken from interviews with informants totaling 5 people and had varying levels of education starting from S-1, SMA, and SMK.  This research uses qualitative methods with a phenomenological approach, with data collection techniques through observation, interviews, and documentation. The data obtained was then analyzed by data reduction, data display, and determining conclusions. The results showed that the five informants interviewed had experienced Postpartum syndrome that occurred after giving birth. Postpartum syndrome occurs due to the inability to manage emotional control and lack of knowledge when giving birth in the first child phase. The resilience built by mothers in Dusun V Cempaka Laut Dendang are: 1) acceptance of conditions and self-education; 2) self-acceptance and awareness of the natural postpartum process; 3) emotional support from husband; 4) full support from husband and family; and 5) support from husband and in-laws. The results of this study as a reference for information in dealing with postpartumsyndrome that occurs in mothers who have just given birth.